Detection of Eye Pressure Disease Using ViT-Based Hybrid Learning Methods - Kaya, Mahmut; Bilgen, Yusuf (Düzce Üniversitesi, 2025)
Glaucoma is a disease that occurs after a certain age due to damage to the optic nerves. Today, machine learning methods can be successfully applied to detect such diseases. Instead of using the image data directly, the classification process is carried to a new representation space, which positively affects the classification performance. In this study, principal component analysis (PCA), linear discriminant analysis (LDA) and vision transformation (ViT) methods are used for feature extraction. In addition, CLAHE filtering technique before ViT B16 was used in one of the proposed models. The classification process was performed with six different models using these methods alone or in combination, and the results are presented comparatively. Fine Tune ViT-PCA-SVM and Fine Tune ViT-LDA-SVM models achieved 92% classification success. As a result, the combination of ViT, which is a deep learning method, and PCA or LDA, which are machine learning methods, as feature extraction methods increased the classification success.

Glokom, belirli bir yaştan sonra görme sinirleri üzerinde oluşan bir hasardan dolayı ortaya çıkan bir rahatsızlıktır. Bu tür hastalıkların tespitini yapmada günümüzde makine öğrenmesi yöntemleri başarıyla uygulanabilmektedir. Görüntü verilerinin doğrudan kullanımı yerine yeni bir temsili uzaya taşınarak sınıflandırma işleminin gerçekleştirilmesi sınıflandırma performansını olumlu etkilemektedir. Bu çalışmada öznitelik çıkartmada temel bileşen analizi (PCA), doğrusal ayırım analizi (LDA) ve görü dönüştürücü (ViT) yönteminden yararlanılmıştır. Ayrıca önerilen modellerden birinde ViT B16 öncesi CLAHE filtremele tekniği kullanılmıştır. Bu yöntemlerin tek başına veya bir araya getirildiği altı farklı model ile sınıflandırma işlemi gerçekleştirilmiş olup sonuçlar karşılaştırmalı olarak verilmiştir. Fine Tune ViT-PCA-SVM ve Fine Tune ViT-LDA-SVM modelleri %92 oranında sınıflandırma başarısı elde etmiştir. Sonuç olarak derin öğrenme yöntemi olan ViT ve makine öğrenmesi yöntemlerinden olan PCA veya LDA’nın öznitelik çıkartma olarak bir arada kullanıldığı yöntemler sınıflandırma başarısını arttırmıştır.
ViT Tabanlı Hibrit Öğrenme Yöntemleri ile Göz Tansiyonu Hastalığının Tespiti
Keywords: Neural Networks; Nöral Ağlar; Machine Learning Algorithms; Makine Öğrenmesi Algoritmaları